2022
DOI: 10.1021/acs.langmuir.1c03347
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable N2/Water Foams Stabilized by Dilute Nanoparticles and a Surfactant at High Salinity and High Pressure

Abstract: The rapid development of unconventional oil and gas resources presents challenges for foam flooding for reservoirs with high salinity and high heterogeneity at elevated temperatures. In this study, hydrophilic anionic sulfonate-modified nanoparticles (NPs) exhibited a synergistic effect with a cationic surfactant in stabilizing N 2 /water foam in the presence of concentrated divalent ions from ambient temperature up to 70 °C. With low concentrations of both the sulfonated NPs (SNPs) and cationic surfactant, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Long‐term foam stability was measured by the same method as past studies (Adkins et al, 2010; Alzobaidi, Da, et al, 2021; Chen et al, 2023; Da et al, 2022; Zhu et al, 2022). Once isolated in the view cell, foam was observed over time with a Nikon microscope camera.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term foam stability was measured by the same method as past studies (Adkins et al, 2010; Alzobaidi, Da, et al, 2021; Chen et al, 2023; Da et al, 2022; Zhu et al, 2022). Once isolated in the view cell, foam was observed over time with a Nikon microscope camera.…”
Section: Methodsmentioning
confidence: 99%
“…There has been extensive research in recent years on developing stable foams. “Ultra‐stable” foams—with coarsening rates of about 100 μm 3 /min—have been designed with N 2 (Da et al, 2022; Singh & Mohanty, 2015; Zhu et al, 2022). Unfortunately, differences in chemistry and solubility make N 2 results difficult to translate to CO 2 foams.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the combination of multiple displacement technologies to increase recovery has been evaluated and proven more effective. For example, water alternating gas (WAG) flooding, nanoparticle/nanofluid-assisted water alternating gas (NWAG) flooding, NPs and polymers synergistic combination, NPs assisting foam flooding, NPs assisting surfactant flooding, surfactant alternating gas (SAG) flooding, ,, alkaline surfactant alternated gas (ASAG) flooding, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial rheology can thus be employed in characterizing the ability of an interface to resist distortion and deformation, key factors when attempting to control the thin film drainage and retard or arrest bubble coarsening in foams [76,77]. For instance, Zhu et al [78] studied the dilational rheological properties of interfaces in presence of hydrophilic anionic sulfonate-modified nanoparticles (28.5 ± 0.2 nm) in tandem with the cationic surfactant Arquad 12-50 using pendant drop tensiometry. It was shown that while the surfactant-laden gas-liquid interface exhibited a negligible storage dilatational modulus κ s ′ ∼ 0-10 mN m −1 , for surfactant concentration of 0.01-0.1 wt.%, the addition of 0.1 wt.% particles to the droplet containing 0.01 wt.% surfactant led to an enhancement in the modulus, κ s ′ ∼ 20 mN m −1 .…”
Section: Introductionmentioning
confidence: 99%